2014
DOI: 10.1074/jbc.m114.553065
|View full text |Cite
|
Sign up to set email alerts
|

Generating Symmetry in the Asymmetric ATP-binding Cassette (ABC) Transporter Pdr5 from Saccharomyces cerevisiae

Abstract: Background: Fungal multidrug efflux pumps possess a degenerate nucleotide-binding site (NBS). Results: Restoring all the nonconserved amino acids in the degenerate NBS of Pdr5 leads to complete loss of function of the protein. Conclusion:The degenerate NBS is essential and acts as a structural platform supporting the canonical NBS. Significance: This is the first study dealing with the entire degenerate NBS and its functional role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 35 publications
1
42
0
1
Order By: Relevance
“…Thus, their observations indicate that Snq2p and Pdr5p share common substrates, but also have specificities. The relationships between Pdr5p structure and activity have been extensively studied, 20,[28][29][30][31][32] but the structure-function relationships of Snq2p have not been reported. Therefore, it is interesting and important to compare Snq2p and Pdr5p for improving our understanding of ABC transporters.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, their observations indicate that Snq2p and Pdr5p share common substrates, but also have specificities. The relationships between Pdr5p structure and activity have been extensively studied, 20,[28][29][30][31][32] but the structure-function relationships of Snq2p have not been reported. Therefore, it is interesting and important to compare Snq2p and Pdr5p for improving our understanding of ABC transporters.…”
Section: Discussionmentioning
confidence: 99%
“…The deviant Walker A substitution C199A was phenotypically WT. These results strongly suggested that the deviant ATP site is non-catalytic, an observation clearly supported by further work with Pdr5 [23,24]. The big surprise, however, was the behaviour of the alanine substitution in the highly conserved His 1068 of the H-loop.…”
Section: Important Features Of the Pdr5 Transportermentioning
confidence: 64%
“…Why such a substitution would appear in the N242K suppressor hunt was a mystery. However, subsequent work demonstrated that the atypical ATP site is heavily involved in signal transmission [23,24]. …”
Section: The Signal Interface Of Pdr5 Shares Some Features With Its Smentioning
confidence: 99%
See 2 more Smart Citations